2g+7g=-4g+7+6g

Simple and best practice solution for 2g+7g=-4g+7+6g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g+7g=-4g+7+6g equation:


Simplifying
2g + 7g = -4g + 7 + 6g

Combine like terms: 2g + 7g = 9g
9g = -4g + 7 + 6g

Reorder the terms:
9g = 7 + -4g + 6g

Combine like terms: -4g + 6g = 2g
9g = 7 + 2g

Solving
9g = 7 + 2g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-2g' to each side of the equation.
9g + -2g = 7 + 2g + -2g

Combine like terms: 9g + -2g = 7g
7g = 7 + 2g + -2g

Combine like terms: 2g + -2g = 0
7g = 7 + 0
7g = 7

Divide each side by '7'.
g = 1

Simplifying
g = 1

See similar equations:

| 2(2x-5)=7+6x | | 3x^2-10xy+3y^2+8=0 | | y/15=-27 | | x/4+3x=26 | | 0=x^2-9x-9 | | 5ln(8x)=25 | | x+(.2x)+20=332 | | 175x=60000 | | -1.8x+5.4=-1.8(x-3) | | (1/4^2)/5/7 | | f(x)=-4x+5 | | 6x^3-60x^2+150x=0 | | (1/4)^2/5/7 | | 32x^7-28x^4/4x^3 | | 16y-36x^2y= | | 1.4x-3-0.9x=12.5 | | (1x-1x)+2=1 | | -12x+(-4)=32 | | 3.8q-4.8-5.4q=-2.6q-2.2 | | 10(t-6)+8t=6(3t+4)-11 | | X+(.2x)=332 | | 4/9/(-7/3) | | 3.8q-4.8-5.4q=2.6q-2.2 | | 9x=2x+5 | | 91-(4x+13)=4(x+6)+x | | 15x-8=9x+4 | | 94+7x=114+5x | | x/15-5=x/15+5+0.5 | | 0.666666666x+x/3 | | 99+9x=117+6x | | 4(3+x)-2=2(x-4) | | 99+9x=117+6 |

Equations solver categories